Summary analysis of the deformations of the control GNSS network of the "Mandici" landslide using robust methods - Bošković, Vladan; Pejović, Milutin (Tehnika (Beograd), 2023)
The subject of the paper is the description and application of robust methods of deformation analysis for the purposes of determining the stability of the GNSS control network of the "Mandići" landslide. The paper provides a concise description of the mathematical model of robust methods as well as the procedure for robust evaluation of displacement vectors. A robust estimation of the displacement vectors in the work was performed on the simulated data using L1, L1-L2 , Lp and the Danish objective function. At the end of the paper, the results of the mentioned functions were summarized and compared with the simulated values.